2021
DOI: 10.1038/s41467-021-24842-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-fast single-crystal polymerization of large-sized covalent organic frameworks

Abstract: In principle, polymerization tends to produce amorphous or poorly crystalline materials. Efficiently producing high-quality single crystals by polymerization in solvent remains as an unsolved issue in chemistry, especially for covalent organic frameworks (COFs) with highly complex structures. To produce μm-sized single crystals, the growth time is prolonged to >15 days, far away from the requirements in practical applications. Here, we find supercritical CO2 (sc-CO2) accelerates single-crystal polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 54 publications
1
56
0
1
Order By: Relevance
“…Majority of the reported COF membranes are assembled using this one-step procedure, predominantly in liquid phase using interfacial (oil–water biphasic system) or in-situ solvothermal (monophasic system) methods 30 . In liquids, controlling the concurrent polymerization and crystallization during membrane formation is quite challenging; primarily due to the high surface tension (2 × 10 −2 −5 × 10 −2 N m −1 )) and viscosity (0.3–4 cp) of liquids which makes the removal of by-product from the reaction site extremely difficult 31 , 32 . Consequently, the concentration of reacting monomers is low near the polymerization sites whereas that of byproducts is higher, leading to hindered reaction reversibility 20 , 33 , 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the reported COF membranes are assembled using this one-step procedure, predominantly in liquid phase using interfacial (oil–water biphasic system) or in-situ solvothermal (monophasic system) methods 30 . In liquids, controlling the concurrent polymerization and crystallization during membrane formation is quite challenging; primarily due to the high surface tension (2 × 10 −2 −5 × 10 −2 N m −1 )) and viscosity (0.3–4 cp) of liquids which makes the removal of by-product from the reaction site extremely difficult 31 , 32 . Consequently, the concentration of reacting monomers is low near the polymerization sites whereas that of byproducts is higher, leading to hindered reaction reversibility 20 , 33 , 34 .…”
Section: Introductionmentioning
confidence: 99%
“…[252,253] Many synthetic methods have been developed for the formation of 2D and 3D COFs, such as solvothermal, microwave, ionothermal, interfacial, and room-temperature methods. Solvothermal methods involve the reversible reaction of soluble monomers in a Pyrex tube of suitable volume at high temperatures (>100 °C), after degassing by multiple freeze-pump-thaw cycles, [254,255] whereas microwave methods are used to rapidly synthesize crystalline COFs within a short reaction time (<1 h). [256] An example of an ionothermal method is the synthesis of covalent triazine frameworks in molten ZnCl 2 (as the solvent), where the latter also mediates the required trimerization reaction, [257] whereas the interfacial method involves the synthesis of COFs as thin films at the interface of two immiscible solvents.…”
Section: Opportunities For the Use Of Icofs In Energy Devicesmentioning
confidence: 99%
“…Since then, COFs with different linkages and topologies have been synthesized one after another by various approaches including solvothermal, [6][7][8][9] ionothermal, 10,11 microwave, 12,13 atmospheric solution, [14][15][16][17][18] mechanochemical, [19][20][21] electrochemical, 22,23 photochemical, 24,25 and other methods. [26][27][28][29] The CURATED-COFs database 30 showed that the query string TITLE-ABS-KEY (''Covalent Organic Framework'') retrieved over 4300 research papers and close to 1000 patents, covering various subject areas such as chemistry, materials science, chemical engineering, and environmental science. 31 The diverse linkage chemistry of COFs is the basis not only for investigating the structure-property relationship, but also for expanding the applications of COFs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, COFs with different linkages and topologies have been synthesized one after another by various approaches including solvothermal, 6–9 ionothermal, 10,11 microwave, 12,13 atmospheric solution, 14–18 mechanochemical, 19–21 electrochemical, 22,23 photochemical, 24,25 and other methods. 26–29 The CURATED-COFs database 30 established by Smit et al has included 648 COFs as of June 2021. The variety of COFs has been still increasing rapidly since the release of this archive to date.…”
Section: Introductionmentioning
confidence: 99%